Elevation Dynamics and Thermal Variations During the Eruption Phases of Mount Lewotobi Laki-laki - Khusnani, Azmi; Jufriansah, Adi; Pramudya, Yudhiakto; Wahab, Dedi Suwandi; Alip, Isma; Samana, Fazaki Ramadhani Anwar; Sina, Tuti Asmianti; Servia; Deti, Maria (The Indonesian Institute of Science and Technology Research, 2025)
Mount Lewotobi Laki-Laki since December 2023, the eruption status has increased, with a substantial increase in November 2024. This led to modifications in the distribution of temperature, the patterns of volcanic material flow, and the morphology of the land. The objective of this research was to examine the relationship between the elevation profiles and temperature fluctuations that occurred during the eruption of Mount Lewotobi Laki-Laki. This investigation illustrates the considerable impact of volcanic activity on the environment by employing satellite data-based methodologies, digital elevation models (DEMs), and thermal analysis. The results suggest that volcanic activity has a significant impact on the distribution of temperature and the alteration of geological structures. The observed temperature increase, which extends from the crater to the slopes and lowlands, has an impact on local ecosystems and atmospheric conditions. The precipitous elevation profile significantly impacts the flow pattern of volcanic material, such as lava and lahars, which can pose a disaster risk to settlements and community activities in the vicinity. This research underscores the necessity of ongoing monitoring for risk mitigation and community preparedness in volcanic disasters.